Análise da interação terapêutica em intervenções com universitários com transtorno de ansiedade social - Garcia, Vagner Angelo [UNESP] (2014)
The study of the therapeutic interaction is described as a possiblity to understand what terapists do to prodece change as well as to describe how clients behave during a psychotherapy session. This type of study can be conducted by the description of therapist and client behavior categories as well as the subject discussed by both. This way of research contributes to the development of the therapeutic process and to the training of future therapists. This study aimed to analyze behavioral therapy sessions with college students with social anxiety disorder. Twenty-two sessions of two clients were analized and categorized according to the Multidimensaional Categorization System of Therapeutic Interaction Bahaviors (SiMCCIT). The sessions were analyzed by two observers, who preceded training for agreement on the use of the system, from which satisfactory levels were achieved according to two indicators: Kappa statistics and percent agreement. The results are presented in three studies. For Studies I and II, after the analysis and organization of categories in terms of frequency and duration, the sessions analyzed were grouped according to the moment of the therapeutic process: Start (first three sessions), Development (five intermediate sessions) and Closure (final three sessions). Study I described in terms of frequency and duration the behavior categories of therapists and client. The therapist role was characterized by stimulating the client's report throughout all terapy in a high frequency (categories of Facilitation and Gestures of Agreeement), by informing in greater frequency and intensity (t) at the beginning of therapy and by requesting reflextion, interpreting, recommenging and approving with approximate averages during all de intervention. Client's behavior categories demonstrated that clientes with social anxiety disorder showd no significant oppositonal and... (Complete abstract electronic access below)